Nonsurgical Management of Adductor-related groin pain with Ultrasound-Guided Platelet-Rich Plasma Injection and Physical Therapy in a Competitive Soccer Player: A Case Report - Giorgio Zeppieri; Micheal S Smith; Ryan P. Roach (International Journal of Sports Physical Therapy)
# Introduction